Walking and standing in Athinas Street: Encountering pedestrian life in Athens’ historical centre - Dimitra Kanellopoulou (Ambiances)
Over the last three decades the centre of Athens has been the site of numerous pedestrianisation projects, transforming the image and function of Athenian public space within a four square kilometre zone around Acropolis Hill. Local authorities largely promote pedestrianisation as a means of boosting the cultural tourist profile of the Greek capital. Surrounded by streets that are replete with tourist and commercial activities, Athinas Street has been the focus of discussions on future pedestrianisation since 2009. In the context of a growing debate on the need of radical gestures in order to stimulate life in public space, the paper aims to stimulate discussion about the forms and triggers of animation of street life that do not depend on traditional planning or event management. By means of close observation of walkers’ itineraries, the study seeks to reveal the ways in which street life flourishes within a blend of pedestrians’ different types of presence in public associated with the permeable boundaries between private and public space usage. The author, who takes an urban planning and ethnographic perspective, aims to contribute to the current growing debate in Europe on the transformation of public space through the promotion of environments that promote walking. The article suggests that the enlivening of public space thrives in Athinas Street thanks to a heterogeneous walkscape characterised by a diversity of practices, trajectories and profiles of walkers, all of whom contribute to enlivening the place and creating a local identity.